2021
DOI: 10.1111/hex.13341
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of self‐care during the COVID‐19 pandemic among individuals with rheumatoid arthritis: A qualitative study

Abstract: Objectives This study aimed to explore the impact of the coronavirus disease 2019 (COVID‐19) pandemic on self‐care of individuals living with rheumatoid arthritis (RA). Methods Guided by a constructivist, qualitative design, we conducted one‐to‐one in‐depth telephone interviews between March and October 2020 with participants with RA purposively sampled for maximum variation in age, sex and education, who were participating in one of two ongoing randomized‐controlled trials. An inductive, reflexive thematic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 40 publications
3
21
0
1
Order By: Relevance
“…Nevertheless, other participants in our study experienced that more time at home and fewer social obligations during the pandemic created the opportunity for more exercise and improved sleep. These findings are supported by Leese et al, who described how some patients with RA were able to improve their self-care while spending more time at home [35].…”
Section: Discussionsupporting
confidence: 66%
“…Nevertheless, other participants in our study experienced that more time at home and fewer social obligations during the pandemic created the opportunity for more exercise and improved sleep. These findings are supported by Leese et al, who described how some patients with RA were able to improve their self-care while spending more time at home [35].…”
Section: Discussionsupporting
confidence: 66%
“…Participants reported a lack of confidence in self-monitoring and symptom interpretation when contributing to virtual consultations. Leese et al (2021) have reported that some people with rheumatoid arthritis experienced an improvement in their self-care practices while remaining at home. However, Massouh et al (2020) reported that self-efficacy/confidence is a key determinant in self-care, enhanced by social support and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…For decades, community-based participatory action researchers have intentionally partnered with community collaborators to identify research questions and priorities toward addressing a particular health or social issue; the Canadian Journal of Occupational Therapy (CJOT) has published several studies of this nature (see, for example, Turcotte et al, 2019). While participatory research methods typically describe the roles of community partners as an explicit step, this element can also be integrated into other research designs, including qualitative methodologies (e.g., Leese et al, 2021) and multi-national clinical trials (e.g., Fletcher et al, 2018).…”
Section: Patient and Community Engagementin Researchmentioning
confidence: 99%
“…Si, normalement, les méthodes de recherche participative décrivent explicitement les rôles des partenaires de la communauté, cet élément peut également être intégré dans d’autres devis de recherche, y compris les méthodologies qualitatives (p. ex. Leese et al, 2021) et les essais cliniques internationaux (p. ex. Fletcher et al, 2018).…”
Section: Engagement Des Patients Et De La Communauté Dans La Rechercheunclassified